Evaluation of combined semi-humid chemo-mechanical pretreatment of lignocellulosic biomass in energy efficiency and waste generation - Chuetor, Santi; Champreda, Verawat; Laosiripojana, Navadol (Bioresource technology, 2019)
[Display omitted] •A combined chemo-mechanical pretreatment of lignocellulosic biomass could be an alternative pretreatment process which could be potentially suitable for agro-industries compared to the conventional processes.•Study of energy efficiency (kg of product/unit of energy consumption) is a crucial step to evaluate the performance of developed process comparing to conventional method.•Study of waste generation (kg of waste generated/kg of product) is also an important factor for wastes management in the valorization of lignocellulosic feedstocks.•Obtained results have been interesting in term of energy efficiency and waste generation of combined semi-humid chemo-mechanical pretreatment of lignocellulosic biomass for biofuel production. A combination of chemo-mechanical pretreatment of lignocellulosic biomass was developed with objectives to evaluate and optimize the energy efficiency and waste generation occurred in the pretreatment process. Sugarcane bagasse (SCB) was chemically pretreated with alkaline and alkaline peroxide followed by mechanical size reduction and enzymatic hydrolysis. The high solid and low solid loading pretreatments were studied to compare the total energy consumption, energy efficiency as well as waste generation. SCBSHNa (1:5) namely semi-humid chemo-mechanical pretreatment was found as the most effective pretreatment by decreasing 65% of total energy consumption. Moreover, the SCBSHNa (1:5) achieved the highest energy efficiency resulting in 0.536 kg reducing sugars/kWh and generated 0.33 kg of waste/kg reducing sugars. The developed process represented the advantages on energy efficiency and less waste generation compared to the conventional chemical soaking pretreatment process.